Prevalence and factors associated with burnout among healthcare providers at Kasulu district in Kigoma region, 2024: an analytical cross-sectional study in a primary healthcare setting - Omary Ubuguyu; Godbless Henry Mfuru; Khadija I Yahya-Malima (BMJ Open)
Background Burnout among healthcare providers affects their well-being and quality of care. Despite its importance, limited data exist on burnout among primary healthcare providers in Tanzania.Objectives To determine the prevalence of burnout and associated factors among healthcare providers in Kasulu district, Kigoma region, 2024.Study design Analytical cross-sectional study conducted from January to June 2024.Study setting Primary health facilities at Kasulu district in Kigoma region.Participants Healthcare providers working in Kasulu district for more than 6 months before study.Primary outcome Burnout.Results Among 266 healthcare providers with a response rate of 99%, 59.4% were male. The median age was 32 years (IQR 27–37). Burnout prevalence was 54.5% (95% CI 48.5% to 60.4%), higher among nurses (61.3%), those living off-site (69.6%) and those considering leaving their careers (86.2%). Significant factors included age 21–30 years (adjusted prevalence ratio (aPR) 1.55, 95% CI 1.06 to 2.27), nursing profession (aPR 2.19, 95% CI 1.07 to 4.48), off-site residence (aPR 1.23, 95% CI 1.02 to 1.49), 6 months to 2 years of experience (aPR 1.44, 95% CI 1.12 to 1.86), dissatisfaction with salary (aPR 1.77, 95% CI 1.02 to 3.07), poor colleague relationships (aPR 1.25, 95% CI 1.03 to 1.51), ≥4 night shifts/week (aPR 2.54, 95% CI 1.33 to 4.86), attending ≥41 patients per day (aPR 1.52, 95% CI 1.06 to 2.19) and lack of academic growth opportunities (aPR 1.62, 95% CI 1.15 to 2.29).Conclusion Rural settings like Kasulu face unique challenges, including limited resources and heavy workloads, exacerbating burnout among healthcare providers. Over half of healthcare providers experienced burnout, with younger providers, nurses, those living off-site, less experienced staff, poor colleague relationships and high patient loads at higher risk. To mitigate burnout, authorities should provide career counselling, onsite housing, mental health support and increased staffing.